Influence of Topping and Spacing on Growth, Yield, and Fruit Quality of Tomato (Solanum lycopersicum L.) Under Greenhouse Condition - Nkansah, George Oduro; Amoatey, Christiana; Zogli, Michael Kwaku; Owusu-Nketia, Stella; Ofori, Peter Amoako; Opoku-Agyemang, Frank (Frontiers in Sustainable Food Systems, 2021)
Tomato is an important vegetable in Ghanaian diet and contributes enormously in livelihood improvement. Tomato production is threatened by high prevalence of biotic and abiotic stresses as well as increased post-harvest losses and poor agronomic practices thereby resulting to massive importation of tomato and its products to meet the local demands. The recent introduction of greenhouse vegetable cultivation technology in Ghana is a sustainable attempt in addressing and ensuring year-round production of vegetables including tomato. However, research on agronomic practices targeted to improving yield and fruit quality under greenhouse condition in Ghana is scarcely available. Therefore, this study seeks to evaluate the effect of plant spacing and topping on tomato yield and fruit quality under greenhouse conditions. A 3×3 factorial treatments arranged in a completely randomized design (CRD) with three replications was used. Two factors; plant spacing and topping with each having three levels were used. Thus, the levels for plant spacing were 0.15 m x 1.3 m, 0.2 m x 1.3 m and 0.3 m x 1.3 m whiles topping treatments at trusses 2, 3, and 4 (control) were done. The results showed that yield was significantly influenced by plant spacing in both experiments. The interaction effect of 0.2 m x 1.3 m plant spacing and topping at truss 2 showed significantly higher yields. Furthermore, juice volume was significantly increased by plant spacing. Again, 0.2 m x 1.3 m plant spacing by truss 2 topping interaction produced the highest juice volume. Therefore, these agronomic practices could be an essential and effective approach in achieving higher tomato production with improved fruit quality under greenhouse cultivation to ensure sustainable food security.